Opinion of Croatian consumers on traditional Dalmatian lamb in the process of obtaining a PDO label - Martić Kuran, Linda (Array, 2021)
The protection of Dalmatian lamb ("Dalmatinska janjetina") with a protected designation of origin label (PDO) is based on the specific quality of meat of Dalmatian pramenka lamb and the traditional lamb breeding method in the geographic area that coincides with the breeding area of Dalmatian pramenka (indigenous Croatian sheep breed). Under the name of "Dalmatinska janjetina", only the meat of lambs of Dalmatian pramenka, bred exclusively in Dalmatia, can be placed on the market. In the process of obtaining a PDO label, which has recently been completed at the Croatian national level and is currently in the process at the EU level, a survey among Croatian consumers (a sample of 1,034 consumers from all over Croatia) was conducted to determine the recognition of this product on the Croatian market, as well as consumer preferences considering similar products from other Croatian regions. The research has shown that Croatian consumers recognize Dalmatian lamb as a traditional, high-quality product. Thus, almost 75 % of the respondents recognize it as a particular type of lamb of better quality than others on the Croatian market. Almost 85 % of the respondents use lamb regardless of type in their diet, but more than 58 % always on special occasions (folk festivals and family celebrations), especially if prepared in the traditional way (lamb on a spit) by which Dalmatia as a region is recognized by more than 85 % of the respondents. The market reputation and connection with the geographic production area are why Croatian consumers rather buy Dalmatian lamb over others.